Intellectual capital and firm performance in the Indonesian banking sector: A post-pandemic reassessment - Abygail Flower Sigar; Agus T. Poputra; Lidia M. Mawikere (Yayasan Widyantara Nawasena Raharja, 2026)
Prior studies on intellectual capital and firm performance report inconsistent findings, particularly in the banking sector, where reliance on intangible resources is high yet operations are increasingly automated through digital technology. This study re-examines that relationship by testing the effect of human capital and relational capital on the performance of banking companies listed on the Indonesia Stock Exchange during the 2022-2024 period, a period marked by accelerated digital transformation in the industry. Human capital is proxied using value added human capital (VAHU), relational capital using relational capital efficiency (RCE), and company performance using return on assets (ROA). Using a quantitative causal-associative design, 84 firm-year observations were selected through purposive sampling and analyzed using multiple linear regression. The results show that neither human capital nor relational capital has a significant effect on company performance, with the two variables jointly explaining only 2.2% of the variation in ROA. These findings suggest that in an increasingly digitalized banking industry, traditional intellectual capital components alone are insufficient to explain firm performance, and that operational, risk-based, and technological factors likely play a more dominant role. The study contributes to Resource-Based Theory by highlighting boundary conditions under which intangible resources fail to translate into measurable financial performance, and offers practical implications for banking companies in reassessing their intellectual capital management strategies.